Selection of magister learners in nursing science at the Rand Afrikaans University - A Botes (AOSIS, 2001)
Selection of learners implies that candidates are assessed according to criteria with the purpose of selecting the most suitable learners for the course. A magister qualification is on level 8A of the National Qualifications Framework (NQF). The purpose of a magister qualification in Nursing is the development of advanced research, clinical, professional, managerial, educational, leadership and consultative abilities (knowledge, skills, values and attitudes) for the promotion of individual, family, group and community health. From the above introduction it becomes clear that there is a high expectations of a person with a magister qualification. Such a person should be a specialist, scientist, leader and role model in the profession. A magister programme is human-power intensive as well as capital intensive for both the learner and higher education institutions. It is therefore important to select learners with the ability to achieve the outcomes of the programme. Limited research has been conducted on the selection of post graduate learners.